LEO multi-service routing algorithm based on multi-objective decision making - Li YANG; Jing SUN; Cheng-sheng PAN; Qi-jie ZOU (Tongxin xuebao)
In low earth orbit(LEO) satellite networks,in view of the unbalanced link resource,it's difficult to meet differentiated quality of service(QoS) requirements and easily lead to reduce the efficiency of the whole network.A routing algorithm based on multi-objective decision making was proposed which defined LEO satellite network transmission service as the delay sensitive,sensitive bandwidth and reliability sensitive three categories.It used the eigenvector method to calculate service weights,and used the consistency ratio to determine whether it can be accepted.Based on the multi-objective decision making theory,it combined with the actual state of satellite network nodes and links and the specific requirements of the business,calculating the path that meets the QoS requirements of the service,so as to realize the LEO satellite network multi objective dynamic routing optimization.Established simulation platform based on the iridium network system simulated network delay,the uncertain characteristics like the residual bandwidth and packet error rate,route planning for the randomly generated three classes of business.The simulation results show that,the algorithm not only satisfies the QoS constrain while balancing the traffic load of the satellite link effectively,but also improves the performance on the throughput.